Effect of Coriolis Force on the Equillibrium Structures of Rotationally and Tidally Distorted White Dwarf and Prasad Model of Stars - Singla, Aishni (My University, 2012)
In the present thesis an attempt has been made to extend the work of Pathania (37). He studied the effect of inclusion of Coriolis force on the equilibrium structures as well as periods of small adiabatic barotropic modes of oscillations of rotating stars and stars in binary system. Earlier, while computing the effects of rotational and tidal distortions on the equilibrium structures and the eigenfrequencies of radial and non-radial modes of oscillations of rotating stars in binary systems, Mohan and Saxena (29,30) and Mohan et al. (33,34,31,32) did not explicitly account for the effect of Coriolis force and they analyse these problems in inertial frame of reference only. Pathania (37) studied the problems in rotating frame of reference and used the methodology to determine the equilibrium structures of rotationally and tidally distorted polytropic models of stars. In the present study we have tried to investigate the effects of inclusion of Coriolis force on the equilibrium structures of rotationally and tidally distorted White dwarf and Prasad model of stars. Thesis consists of three chapters. Chapter I is introductory in nature. In this chapter we briefly discuss the modified expression for Roche equipotentials incorporates the effect of Coriolis force. The system of differential equation governing the equilibrium structures of rotationally and tidally distorted stars incorporating the effect of Coriolis forces which were earlier developed by Pathania (37), is also discussed. A brief survey of the literature available on the subject and summary of the work presented in the succeeding chapters of the thesis are also given in this chapter. In chapter II we first discuss the concept of white dwarf model of stars and then methodology discussed in chapter II is used to study the equilibrium structures and certain other parameters of rotationally and tidally distorted white dwarf model of stars for different values of 2 0 1 φ as 0.01, 0.05, 0.1, 0.2, 0.5, 0.8. The results thus obtained are compared with the undistorted model in which the effect of Coriolis force has not been there. In chapter III we first discuss the concept of Prasad model of stars and then apply the methodology discussed in chapter II to study the equilibrium structures and certain other parameters of rotationally and tidally distorted Prasad model of stars. Certain conclusion based on the present analysis has also been drawn.
Keywords: Coriolis force, equilibrium structures, rotation, tidal, white dwarf and prasad models of stars